Study on Micro-Nano Pore Characteristics and Classification of Tight Sandstone Reservoir Based on Q-Cluster. (2nd August 2022) - Ge, Jing; Zhao, Wanchun; Wang, Tingting; Cai, Tiantian; Cong, Zhicheng; Bai, Yujie; Gu, Haipeng
Abstract : To realize the quantitative classification and comprehensive evaluation of the tight oil reservoir in the 4th of Quantou Formation in Songliao Basin, the pore structure of tight oil reservoir was quantitatively analyzed. In this study, experiments based on the constant-speed mercury injection, nuclear magnetic resonance, and micron CT are based on the observation of cast thin sections, and scanning electron microscope is conducted. The result shows that a tight oil reservoir space is mainly composed of the intergranular dissolved pore, residual intergranular pore, and intragranular dissolve pore. There are few intercrystalline pore and fracture at the same time. The average pore radius is 1.28 4.58 μ m, and the average throat radius is 0.52 1.27 μ m. Hence, there is a typical micro-nano throat combination with micropores. The pore throat composition and pore structure of reservoirs differ in reservoir with different physical properties. The reservoir quality depends on pore structure especially the throat radius. And the microthroat is a critical factor for permeability. Based on Q-cluster analysis, tight oil reservoirs are classified into three types. The analysis was based on the data such as max throat radius, average throat radius, displacement pressure, median pressure, and permeability. Finally, the reservoirs in the study area are mainly II and I types.